2016
DOI: 10.1021/acs.inorgchem.6b00720
|View full text |Cite
|
Sign up to set email alerts
|

Efficient NiII2LnIII2 Electrocyclization Catalysts for the Synthesis of trans-4,5-Diaminocyclopent-2-enones from 2-Furaldehyde and Primary or Secondary Amines

Abstract: A series of heterometallic coordination clusters (CCs) [Ni(II)2Ln(III)2(L1)4Cl2(CH3CN)2] 2CH3CN [Ln = Y (1Y), Sm (1Sm), Eu (1Eu), Gd (1Gd), or Tb (1Tb)] were synthesized by the reaction of (E)-2-(2-hydroxy-3-methoxybenzylidene-amino)phenol) (H2L1) with NiCl2·6(H2O) and LnCl3·x(H2O) in the presence of Et3N at room temperature. These air-stable CCs can be obtained in very high yields from commercially available materials and are efficient catalysts for the room-temperature domino ring-opening electrocyclization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 70 publications
2
58
0
Order By: Relevance
“…Our philosophy to alter the 3d or the 4f elements in these solution-stable bimetallic 3d/4f species allow us to confirm their stability via EPR and gain useful insights regarding the plausible reaction mechanism via NMR. Moreover, the possibility to tune the organic periphery of these catalysts, 8,25 achieving immobilization, showcases that the present catalysts are highly desirable and the appropriate vehicle to open new avenues in the fields of 3d/4f chemistry and catalysis. Further work is necessary to expand the scope of the present Zn/Ln CCs to other FC alkylation reactions, and this will be the focus of our future activities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our philosophy to alter the 3d or the 4f elements in these solution-stable bimetallic 3d/4f species allow us to confirm their stability via EPR and gain useful insights regarding the plausible reaction mechanism via NMR. Moreover, the possibility to tune the organic periphery of these catalysts, 8,25 achieving immobilization, showcases that the present catalysts are highly desirable and the appropriate vehicle to open new avenues in the fields of 3d/4f chemistry and catalysis. Further work is necessary to expand the scope of the present Zn/Ln CCs to other FC alkylation reactions, and this will be the focus of our future activities.…”
Section: Discussionmentioning
confidence: 97%
“…We showed that a series of isoskeletal 24 M II 2Ln III 2 (M = Co or Ni, Ln = Y, Nd, Eu, Gd, Tb, Dy) CCs, effectively catalyse a domino reaction at room temperature. 8,25 These heterometallic species remain intact in organic solvents and this precise topology brings the 3d and the 4f centres very close (approximately 3.3Å), allowing both metal centres to coordinate to the substrates and promote the coupling reaction in high yield, highlighting the catalytic utility of this tetranuclear bimetallic motif.…”
mentioning
confidence: 99%
“…Interestingly, under these conditions, primary amines afforded the corresponding deprotonated SSs and subsequent acidic treatment gave the corresponding CP. This process is industrially appealing as it allows the reaction to be performed under air and heterogeneous conditions . In 2013, Procopio and co‐workers reported the use of erbium(III) chloride and ethyl lactate (catalyst and solvent, respectively) as a more sustainable alternative .…”
Section: Introductionmentioning
confidence: 99%
“…We recently initiated a project on the synthesis of 3d/4f CCs stabilized by the Schiff base organic ligand H2L [(E)-(2-hydroxy-3-methoxybenzylidene-amino)phenol], that would display catalytic properties [57][58][59]. We also reported the synthesis and characterisation of a series of isoskeletal [60] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In 3d/4f chemistry, only a few polynuclear CCs have been successfully used as homogenous catalysts [54][55][56]. We recently initiated a project on the synthesis of 3d/4f CCs stabilized by the Schiff base organic ligand H2L [(E)-(2-hydroxy-3-methoxybenzylidene-amino)phenol], that would display catalytic properties [57][58][59]. We also reported the synthesis and characterisation of a series of isoskeletal [60] tetranuclear Zn II 2Ln III 2 CCs formulated as [Zn II 2Ln III 2L4(NO3)2(DMF)2] (1Ln) where Ln is Y (1Y), Sm (1Sm), Eu (1Eu) Gd (1Gd), Dy (1Dy), Tb (1Tb) and Yb (1Yb) possessing a defect dicubane topology (Figure 1).…”
Section: Introductionmentioning
confidence: 99%